ETIKA PSIKOANALISIS SIGMUND FREUD SEBAGAI LANDASAN KESALEHAN SOSIAL - Hariyanto, Ishak (AL-TAZKIAH : Journal of Islamic Guidance and Counseling, 2016)
Ethics is the important role in human life, just imagine a world without ethics and morals, then the consequences will be a world where no one has a conscience and no one will ever feel guilty or sorry for what they did or did not do.  According to Freud, he said that human is deterministic because is determined by unconscious irrational power, the unconscious motivation, biological encouragement, and instinctive encouragement. Human has always been the pursuit of perfection to get happiness and to avoid unhappiness. The purpose of this research was to describe about the psychoanalysis ethics of Sigmund Freud and to apply it in social life in order to create the social piety.  During Freud psychoanalysis as if its just in medicine, counseling and religion.  But what about the psychoanalysis ethics of Sigmund Freud are manifesting  in the structure of human personality like Id (Das Es), Ego (Das Ich), Super ego (Das Ueber Ich) were compared in the context of social piety, so it would create the dialogue between individual piety and social piety, to establish the whole system of unity and run circularly.